The economic impact of antimicrobial stewardship programmes in hospitals: a systematic literature review. Issue 4 (August 2019) - Huebner, C.; Flessa, S.; Huebner, N-O.
Summary: Background: Antimicrobial stewardship programmes (ASPs) include strategies that enable sustainable management of rational anti-infective treatment in the clinical setting. The successful introduction of ASPs requires close interdisciplinary collaboration among various health professionals, including the hospital management. So far, ASPs have been evaluated mainly from a clinical–pharmacological and infectious disease perspective. Aim: To identify and evaluate parameters with decisive significance for the economic impact of ASPs. Methods: A systematic literature search for peer-reviewed health-economic studies associated with antimicrobial stewardship programmes was performed. Primary outcomes included savings in drug costs and lower revenue losses for hospitals. Findings and conclusions: A total of 16 studies met all inclusion criteria. Most of the evidence from published clinical trials demonstrated savings through reduced direct cost of antibiotics. However, there are also studies that prove revenue effects of ASPs through decreases in length of stay and readmission rates.